Proceedings of the 2019 Conference of the North 2019
DOI: 10.18653/v1/n19-1061
|View full text |Cite
|
Sign up to set email alerts
|

Lipstick on a Pig:

Abstract: Word embeddings are widely used in NLP for a vast range of tasks. It was shown that word embeddings derived from text corpora reflect gender biases in society. This phenomenon is pervasive and consistent across different word embedding models, causing serious concern. Several recent works tackle this problem, and propose methods for significantly reducing this gender bias in word embeddings, demonstrating convincing results. However, we argue that this removal is superficial. While the bias is indeed substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 5 publications
(15 reference statements)
1
47
0
Order By: Relevance
“…Figure 7 shows the result of applying the debiasing technique, highlighting that some of the spurious correlations have indeed been removed. It is important to note though, that the above technique does not reliably remove all relevant bias in the embeddings and that bias is still measurably existing in the embedding space as Gonen and Goldberg (2019) have shown. This can be verified with whatlies, by plotting the neighbours of the biased and debiased space: As the output shows, the neighbourhoods of maid in the biased and debiased space are almost equivalent, with e.g.…”
Section: Emb_of_pairsplot_distance(metric="cosine")mentioning
confidence: 99%
“…Figure 7 shows the result of applying the debiasing technique, highlighting that some of the spurious correlations have indeed been removed. It is important to note though, that the above technique does not reliably remove all relevant bias in the embeddings and that bias is still measurably existing in the embedding space as Gonen and Goldberg (2019) have shown. This can be verified with whatlies, by plotting the neighbours of the biased and debiased space: As the output shows, the neighbourhoods of maid in the biased and debiased space are almost equivalent, with e.g.…”
Section: Emb_of_pairsplot_distance(metric="cosine")mentioning
confidence: 99%
“…Fairness research in NLP has seen tremendous growth in the past few years (e.g., (Bolukbasi et al, 2016;Caliskan et al, 2017;Webster et al, 2018;Díaz et al, 2018;Dixon et al, 2018;De-Arteaga et al, 2019;Gonen and Goldberg, 2019;Manzini et al, 2019)) over a range of NLP tasks such as co-reference resolution and machine translation, as well as the tasks we studied -sentiment analysis and toxicity prediction. Some of this work study bias by swapping names in sentence templates (Caliskan et al, 2017;Kiritchenko and Mohammad, 2018;May et al, 2019;Gonen and Goldberg, 2019); however they use synthetic sentence templates, while we extract naturally occurring sentences from the target corpus.…”
Section: Related Workmentioning
confidence: 99%
“…Under their evaluation, they find they can nearly perfectly remove bias in an analogical reasoning task. However, subsequent work (Gonen and Goldberg, 2019;Hall Maudslay et al, 2019) has indicated that gender bias still lingers in the embeddings, despite Bolukbasi et al (2016)'s strong experimental results. In the development of their method, Bolukbasi et al (2016) make a critical and unstated assumption: Gender bias forms a linear subspace of word embedding space.…”
Section: Introductionmentioning
confidence: 96%
“…As previously noted, there are now multiple bias removal methodologies (Zhao et al, 2018(Zhao et al, , 2019May et al, 2019) that have succeed the method by Bolukbasi et al (2016). Furthermore Gonen and Goldberg (2019) point out multiple flaws in Bolukbasi et al (2016)'s bias mitigation technique and the aforementioned methods. Nonetheless we believe that this method has received sufficient attention from the community such that research into its properties is both interesting and useful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation